The established chest MRI score for cystic fibrosis can be applied to contrast agent-free matrix pencil decomposition functional MRI: a multireader analysis - Steinke, Eva; Bauman, Grzegorz; Steffen, Ingo G.; Schobert, Isabel T.; Thee, Stephanie; Syunyaeva, Zulfiya; Roehmel, Jobst; Posch, Helena; Fahlenkamp, Ute L.; Scale, Carolin; Veldhoen, Simon; Bieri, Oliver; et al. (Frontiers in medicine, 2025)
Background: Established morpho-functional chest magnetic resonance imaging (MRI) detects abnormalities in lung morphology and perfusion in people with cystic fibrosis (pwCF) using a dedicated scoring system. Functional assessment is performed using contrast-enhanced (CE) perfusion MRI. Novel matrix pencil decomposition MRI (MP-MRI) is a contrast agent-free alternative, but further validation of this technique is needed. Objectives :The aim of this study was to evaluate the applicability of the validated morpho-functional chest MRI score for CE perfusion and MP perfusion MRI in a multireader approach. Methods: Twenty-seven pwCF (mean age 20.8 years, range 8.4-45.7 years) underwent morpho-functional MRI including CE perfusion and MP perfusion MRI in the same examination. Nine blinded chest radiologists of different experience levels assessed lung perfusion and applied the validated chest MRI score to CE- and MP-MRI. Inter-reader agreement of perfusion scores in CE- and MP-MRI were compared with each other and with the MRI morphology score. Differences according to the readers’ experience were also analyzed. Results: The CE perfusion scores were overall lower than the MP perfusion scores (6.2 ± 3.3 vs. 6.9 ± 2.0; p < 0.05) with a strong correlation between both perfusion scores (r = 0.74; p < 0.01). The intraclass correlation coefficient (ICC) as measure for inter-reader agreement was good and significant for both perfusion scores, but higher for the CE perfusion score (0.75, p < 0.001) than for MP perfusion scores (0.61, p < 0.001). The Bland-Altman analysis revealed a difference in CE and MP perfusion scores with more extreme values in CE perfusion scores compared to MP perfusion scores (r = 0.62, p < 0.001). The morphology score showed a moderate to good correlation with the CE perfusion score (r = 0.73, p < 0.01) and the MP perfusion score (r = 0.55, p < 0.01). We did not find a difference in scoring according to the radiological experience level.ConclusionThe established chest MRI score can be applied both to validated CE and novel MP perfusion MRI with a good interreader reliability. The remaining difference between CE and MP-MRI scores may be explained by a lack of routine in visual analysis of MP-MRI and may favor an automated analysis for use of MP-MRI as a noninvasive outcome measure.